THROMBOTIC THROMBOCYTOPENIC PURPURA: OUR CLINICAL EXPERIENCE: Thrombotic Thrombocytopenic Purpura - Baig, Zahid Farooq; Farukh, Aamir; Amir, Mumtaz; Khan, Aslam; Ali, Nadir (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess clinical presentation and outcome of patients with thrombotic thrombocytopenic purpura (TTP) in our setup. Study Design: Descriptive study. Place and Duration of Study: Combined Military Hospital (CMH) Peshawar, from Feb 2016 to Aug 2017. Patients and Methods: In a prospective design, patients diagnosed to be suffering from TTP, were included in this study. Detailed history along with physical examination and thorough investigation of all cases was carried out and collected on proformas. The diagnosis of TTP in our study was done by demonstration of significant schistocytes (more than 1 percent) on peripheral blood film. The patients were treated with steroids and plasma pheresis and in some cases with weekly Rituximab for 4 weeks. The patients were followed up in outdoor clinic on monthly basis. Results: Being a very rare disease, only 11 patients suffering from TTP reported during the study period. They were followed prospectively with a mean duration of follow-up of 11.23 months (± SD 5.57). All patients (100 percent) had anaemia, thrombocytopenia and acute kidney injury. Fever was seen in 54.4% patients and 63.6% patients had neurological involvement. A likely secondary cause of precipitation of TTP was found in 54.5% cases. The mortality rate was 18.2 percent. Conclusion: TTP is a challenging disease for intensive care specialists and can be fatal without effective treatment. A high index of suspicion followed by early diagnosis and prompt treatment can save life. Documentation of deficiency of plasma ADAMTS13 activity is not essential for the diagnosis of TTP and plasmapheresis is the treatment of choice.